Mental Health, Deprivation, and the Neighborhood Social Environment: A Network Analysis. (July 2019) - McElroy, Eoin; McIntyre, Jason C.; Bentall, Richard P.; Wilson, Tim; Holt, Keith; Kullu, Cecil; Nathan, Rajan; Kerr, Andrew; Panagaki, Katerina; McKeown, Mick; Saini, Pooja; Gabbay, Mark; et al.
Different aspects of the neighborhood social environment have been linked with mental ill health; however, the mechanisms underlying these associations remain poorly understood because of the number and complexity of the components involved. We used a novel statistical approach, network analysis, to explore the complex associations between neighborhood social cohesion, social disorder, and mental-health symptoms in a sample of 3, 670 adults from an economically deprived region of the United Kingdom (mean age = 49.34 years, SD = 18.87; 57% female). Elasso regularized networks were estimated, and network comparisons were conducted by level of deprivation. Mental-health symptoms and neighborhood components formed relatively distinct clusters of items. These domains were linked primarily by paranoia, although only in the most deprived group. Drunken/rowdy behavior was particularly influential within the neighborhood cluster; therefore, policies aimed at reducing such disruptive behavior could have positive knock-on effects for social cohesion and mental health.